Scientific workshop Bioassesment of Indonesia Rivers - The Brantas Study Dept. of enviromental engineering FTSP ITS in cooperation with Australian CRC for fresh water ecology ausAID PCI project, Bapedal, kampus ITS, 16 october 1998 - Scientific workshop Bioassesment of Indonesia Rivers - The Brantas Study (16 October: Surabaya) (ITS, 1998)
[74] lembar : il.; 29 cm.